The Biology of Autoimmune Response in the Scurfy Mice that Lack the CD4+Foxp3+ Regulatory T-Cells - Ju, Shyr-Te; Sharma, Rahul; Gaskin, Felicia; Kung, John T.; Fu, Shu Man (Biology (Basel, Switzerland), 2012)
Due to a mutation in the Foxp3 transcription factor, Scurfy mice lack regulatory T-cells that maintain self-tolerance of the immune system. They develop multi-organ inflammation (MOI) and die around four weeks old. The affected organs are skin, tail, lungs and liver. In humans, endocrine and gastrointestinal inflammation are also observed, hence the disease is termed IPEX (Immunodysregulation, Polyendocrinopathy, Enteropathy, X-linked) syndrome. The three week period of fatal MOI offers a useful autoimmune model in which the controls by genetics, T-cell subsets, cytokines, and effector mechanisms could be efficiently investigated. In this report, we will review published work, summarize our recent studies of Scurfy double mutants lacking specific autoimmune-related genes, discuss the cellular and cytokine controls by these genes on MOI, the organ-specificities of the MOI controlled by environments, and the effector mechanisms regulated by specific Th cytokines, including several newly identified control mechanisms for organ-specific autoimmune response.